Infrared response of vanadium oxide (VOx)/SiNx/reduced graphene oxide (rGO) composite microbolometer. (December 2018) - Wu, Zheng-Yuan; Tang, Shiang-Feng; Zeng, Hong-Yuan; Lin, Wen-Jen; Chen, Tzu-Chiang; Gau, Yau-Tang
Abstract: Much attention has been paid to the photoresponse of vanaduim oxide (VOx ) and amorphous silicon based microbolometer for long-wavelength infrared detection under un-cooled operation condition in recent decades. However, the outstanding physical and chemical properties of graphene and reduced graphene oxide (rGO) stimulate their potential for use in light-sensitive applications. Much less attention has been paid to investigate the performance on long-wavelength infrared detection of microbolometer using reduced graphene oxide/SiNx /vanadium oxide composite films deposited on under room temperature operation. In the research, we have proposed the novel microbolometer based on VOx /SiNx /rGO composite films replace the as-deposited VOx based microbolometer. It is noted that such extraordinary properties (high responsivity: 18, 130 V/W and low NETD: 43.32 mK) of the VOx /SiNx /rGO composite presented here encourage us to contemplate on this protocol for next generation optoelectronic device engineering for infrared detection.